2014
DOI: 10.1007/s11010-014-2294-x
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of UVB irradiation induced-apoptosis in cataract

Abstract: Cataract is the most common eye disease that causes blindness in patients. Ultraviolet B (UVB) irradiation is considered an important factor leading to cataract by inducing apoptosis in human lens epithelial cells (HLECs), but the mechanism is currently unclear. In this study, we investigated HLECs under different intensities of UVB irradiation and different exposure time. The annexin V-FITC/propidium iodide staining results showed that UVB irradiation could efficiently lead to HLECs apoptosis in time- and dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 33 publications
3
55
0
Order By: Relevance
“…Previous studies have shown that UVB irradiation could efficiently induce HLECs apoptosis in a time and dose dependent manner [2]. The annexin V-FITC/propidium iodide (PI) staining results revealed that the percentage of primary apoptotic cells in CRTAC1 interfe-rence group was fewer than those in model group and empty vector group (Fig.…”
Section: Inhibition Of Crtac1 Expression Reduced Uvb Irradiation Indumentioning
confidence: 87%
See 3 more Smart Citations
“…Previous studies have shown that UVB irradiation could efficiently induce HLECs apoptosis in a time and dose dependent manner [2]. The annexin V-FITC/propidium iodide (PI) staining results revealed that the percentage of primary apoptotic cells in CRTAC1 interfe-rence group was fewer than those in model group and empty vector group (Fig.…”
Section: Inhibition Of Crtac1 Expression Reduced Uvb Irradiation Indumentioning
confidence: 87%
“…For apoptosis detection, the HLECs were collected and incubated in 5 µL annexin buffer and 5 µL propidium iodide (PI) for 10 min; for ROS detection, the HLECs were incubated with culture medium containing 10 µM DCFH-DA for 30 min; and the HLECs were incubated with Fluo-3 (10 µM, Sigma) for 30 min for determination of intracellular calcium concentration. Additionally, the level of ∆Ψm in HLECs was measured using cationic dye JC-1 assay kit as our previous study [2].…”
Section: Flow Cytometry Analysis Of Apoptosis Ros Production Calciumentioning
confidence: 99%
See 2 more Smart Citations
“…SD rats were subjected to UV irradiation model construction according to the methods described by Ji et al (9). Rats were randomly divided into 2 groups including control group (n=12) and model group (n=48).…”
Section: Methodsmentioning
confidence: 99%